2001
DOI: 10.1111/j.1469-7793.2001.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature has a major influence on cardiac natriuretic peptide in salmon

Abstract: The natriuretic peptide system plays a major role in the fluid and electrolyte homeostasis in vertebrates, based on results from physiological studies (reviewed in Ruskoaho, 1992;Thibault et al. 1999) and experiments with transgenic animals (John et al. 1995;Lopez et al. 1995;Matsukawa et al. 1999). The regulation of the synthesis and secretion of cardiac A-and B-type natriuretic peptides, is, however, still incompletely understood. The ability of salmon (Salmo salar) to maintain volume and electrolyte balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Interestingly, in the ventricle of CA trout, the transcripts of atrial natriuretic peptide B (ANB), myosin light chain 2 and MLP were elevated by about 3-, 3-, and 5-fold, respectively, showing that cold-induced hypertrophy of the fish heart shares several markers with the hypertrophy of the mammalian heart. The increase in mRNA of ANB and its possible association with temperature-dependent increase in the relative heart mass has been recently documented in another salmonid fish (Salmo salar) (43). ANB is produced by hypertrophic ventricular myocytes, and it exerts stabilizing or moderating effect on cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the ventricle of CA trout, the transcripts of atrial natriuretic peptide B (ANB), myosin light chain 2 and MLP were elevated by about 3-, 3-, and 5-fold, respectively, showing that cold-induced hypertrophy of the fish heart shares several markers with the hypertrophy of the mammalian heart. The increase in mRNA of ANB and its possible association with temperature-dependent increase in the relative heart mass has been recently documented in another salmonid fish (Salmo salar) (43). ANB is produced by hypertrophic ventricular myocytes, and it exerts stabilizing or moderating effect on cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ventricular mass of the Burmese python, Python molurus , can increase by 40% after feeding and then return to “normal” following digestion (Andersen et al, 2005 ). The hearts of many fish also show intermittent remodeling in response to seasonal temperature change with chronic cooling during winter triggering ventricular hypertrophy (Farrell et al, 1988 ; Graham and Farrell, 1989 ; Tervonen et al, 2001 ; Klaiman et al, 2011 ; Shiels et al, 2011 ). The hypertrophic trigger in this model is thought to be the increased viscosity of blood at cold (<6°C) temperatures and the hemodynamic stress of pumping this viscous blood (Graham and Farrell, 1989 ; Clark and Rodnick, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mouse models of dilated cardiomyopathy, ANP was found to reduce the chances of heart failure, pathological remodelling and mortality, while maintaining normal systolic function [ 60 ]. A study on salmon cardiac peptides (sCP), which are analogous to ANP and brain natriuretic peptide (BNP) in mammals, found that sCP mRNA increased at lower temperatures, coinciding with heart hypertrophy [ 61 ]. Similar to salmon, we hypothesize from our results that the hibernating thirteen-lined ground squirrel may be relying on ANP to achieve versatile regulation of heart pressure, physiology, and endocrinology.…”
Section: Discussionmentioning
confidence: 99%